Construction of homosexual identity in men: the consumption of (and at) nightclubs - Moraes, José Augusto Mansur (2021)
Objective: This research aims to understand the ways homosexual identities are manifested in young adult men in the context of the consumption of nightclubs, and the goods and services consumed inside these places, in the city of Rio de Janeiro.Method: The research used a qualitative descriptive design, with in-depth interviews. A content analysis was conducted, considering the social context of the interviewees.Originality/Relevance: The research focuses on a diverse group in terms of ethnicity and socioeconomic class and its relationship to a consumer experience mainly of services.Results: Nightclubs – especially those where other minorities are welcome– provide security and shelter for homosexuals, helping to make visible identities that are often made invisible by themselves and much of society. Heterosexuality is used as a standard of comparison for homosexuals to recognize each other, but the places consumed seem to contribute to the weakening of heteronormativity. Within the studied environments, goods, services, and territories are consumed, interacting with the values and ideas of their consumers, generating new meanings for that consumption and extending the identity of those individuals to their possessions of goods and places.Theoretical/methodological contributions: This research contributes to the understanding of the relationship between consumption and the formation and expression of homosexual identities, challenging the research dominant pattern of white socioeconomically privileged males and exploring the socio-cultural dimensions of consumption in the scope of services and goods.